Meningkatkan Kinerja Guru PAI Melalui Kepemimpinan Kepala Sekolah - Abdul Wahid; Iin Zainab (AFKARINA: Jurnal Pendidikan Agama Islam, 2021)
Abstract: This study aims to describe Principal Leadership in Improving Teacher Performance at MTs Nurul Qadim Paiton. This research uses a qualitative descriptive with a case study research type. The subjects in this study were the principal and teachers. Data collection techniques in this study used observation, interviews and document studies. The data analysis technique is by data reduction, data presentation and conclusion. While testing the validity of the data using triangulation techniques. The results of this study indicate that the principal's leadership in improving teacher performance at MTs Nurul Qadim Paiton is shown in the form of task-oriented and relationship-oriented principal behavior. Task orientation is carried out in the form of supervision and the provision of sanctions and rewards. Meanwhile, relationship orientation is carried out in the form of exemplary, attention to subordinates, and providing training.